Civilizational Basis of National Integration in India - Prazauskas, Algis (Acta Orientalia Vilnensia, 2003)
During the last decade, the concept of civilization as applied to the study of international relations, has become a controversial issue in political science. This article attempts at examining the relationship between civilization and the process of national integration of a multiethnic state. Considering the history of the country, the size and diversity of the population, the Indian case is exceptional. However, for the same reasons it provides ample evidence to establish the relationship between specific features of civilization and the formation of supraethnic political culture as a major prerequisite for the stability of a multiethnic polity.